In Praise of Kaleidoscopic Judge: A Different Reading of Judge C. G. Weeramantry’s Jurisprudence Before the Power Politics in ICJ - Punsara, Amarasinghe (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2020)
The power politics has always been a great obstacle in reaching the just consensus in international law. In particular, the political realist approaches stemming from the powerful states often undermine the equality and justice in international legal sphere. Yet the judicial wisdom of some of the outstanding judges in the International Court of Justice have shown a remarkable audacity against trickiest power politics. This article unveils the universalist approach used by outstanding jurist late judge C. G. Weeramantry during his tenure at ICJ. This article seeks how judge Weeramantry delivered his judgements and advisory opinions as a jurist emerged from the Global South. This paper will assess the contribution made by Judge Weeramantry in a complex judicial space filled with power politics from both legal and philosophical perspectives.

Polityka władzy zawsze była wielką przeszkodą w osiągnięciu sprawiedliwego konsensusu w prawie międzynarodowym. W szczególności podejście realizmu politycznego wywodzące się z potężnych państw często podważa równość i sprawiedliwość w międzynarodowej sferze prawnej. Jednak sądownicza mądrość niektórych wybitnych sędziów w Międzynarodowym Trybunale Sprawiedliwości wykazała niezwykłą śmiałość wobec najtrudniejszej polityki władzy. Ten artykuł ujawnia uniwersalistyczne podejście stosowane przez nieżyjącego już sędziego prawniczego C. G Weeramantry’ego podczas jego kadencji w MTS. W tym artykule szukamy sposobu, w jaki sędzia Weeramantry przedstawił swoje wyroki i opinie doradcze jako prawnik wyłoniony z Globalnego Południa. Artykuł ten oceni wkład wniesiony przez sędziego Weeramantry w złożoną przestrzeń sądową wypełnioną polityką władzy, zarówno z prawnego, jak i filozoficznego punktu widzenia.
Pochwała sędziego kalejdoskopowego: inne odczytanie orzecznictwa sędziego C. G Weeramantry’ego przed polityką władzy w MTS
Keywords: universalism; international law; power politics; nuclear weapons; global south; uniwersalizm; prawo międzynarodowe; polityka energetyczna; broń jądrowa; globalne południe